Chinese Herbal Medicine in Ameliorating Diabetic Kidney Disease via Activating Autophagy - Yuyang Wang; Hailing Zhao; Qian Wang; Xuefeng Zhou; Xiaoguang Lu; Tongtong Liu; Yongli Zhan; Ping Li (Journal of Diabetes Research)
Diabetic kidney disease (DKD), a leading cause of end-stage renal disease (ESRD), has become a serious public health problem worldwide and lacks effective therapies due to its complex pathogenesis. Recent studies suggested defective autophagy involved in the pathogenesis and progression of DKD. Chinese herbal medicine, as an emerging option for the treatment of DKD, could improve diabetic kidney injury by activating autophagy. In this review, we briefly summarize underlying mechanisms of autophagy dysregulation in DKD, including AMP-activated protein kinase (AMPK), the mechanistic target of rapamycin (mTOR), and the sirtuin (Sirt) pathways, and we particularly concentrate on the current status of Chinese herbal medicine treating DKD by regulating autophagy. The advances in our understanding regarding the treatment of DKD via regulating autophagy with Chinese herbal medicine will enhance the clinical application of Chinese medicine as well as discovery of novel therapeutic agents for diabetic patients.